Identification of benzydamine and its metabolit in the presence of certain anti-inflammatory non-steroidal drugs - Chorna, Olga; Chornyi, Vasyl; Сhubenko, Oleksandr; Hrubnyk, Ihor; Mishchenko, Volodymyr; Golik, Mykola (ScienceRise: Pharmaceutical Science, 2021)
The aim of the work. Currently, a large number of cases of non-medical use of benzydamine hydrochloride have been described. The identification of benzydamine and its metabolite, benzydamine N-oxide, in the presence of some non-steroidal anti-inflammatory drugs, has been insufficiently studied. Therefore, the development of a method for its identification in biological material is an urgent task. Materials and methods. The subjects of the study were benzydamine hydrochloride and its metabolite, as well as some non-steroidal anti-inflammatory drugs, which are its analogues in terms of pharmacological action. The studies were carried out by methods of thin layer chromatography and high-performance liquid chromatography. Results. At the first stage a screening method for benzydamine identification was studied using the extraction in acidic and basic conditions. It was shown that benzydamine can be isolated in both medias with subsequent development with a solution of iodoplatinate and Dragendorff's reagent according to Munier or with Mandelin reagent respectively. The mobile phase was selected and respective hRf for the target molecule were defined. After a preliminary identification of benzydamine a reference method for the final confirmation of the drug that had led to poisoning was proposed. A robust, specific and accurate reversed phase HPLC method was chosen. It was shown that benzydamine exists in biological material mainly in a form of metabolite – benzydamine N-oxide. The selected method was able to separate and determine key analytes in biological samples after a preparative isolation by TLC method. The comparison with UV spectra of the reference standard of benzydamine hydrochloride was proposed to avoid false positive conclusion of drug identification. Conclusions. Proposed methodology can be applied for routine identification of benzydamine poisoning in toxicological laboratories